A Study to Assess the Prevalence of Tokophobia and the Effect of Nurse-led Intervention on Birth Experience Among Parturients Availing Services in a Tertiary Care Hospital, Kolkata - Maj Linchu P. George; Lt Col Kavita G. (International Journal of Midwifery Nursing And Practices, 2024)
Introduction: Tokophobia, the fear of childbirth, can significantly impact a woman's birth experience and overall well-being. This study aims to determine the prevalence of tokophobia among parturients and evaluate the effectiveness of a nurse-led intervention in improving birth experiences in a tertiary care hospital in Kolkata. Methods: A cross-sectional study design was employed to assess the prevalence of tokophobia among parturients receiving services at the selected tertiary care hospital in Kolkata. The study also included an experimental group that received a nurse-led intervention aimed at addressing tokophobia and enhancing birth experiences. The intervention involved personalized education, counselling, and support provided by trained nurses. Data collection included demographic information, tokophobia assessment, and birth experience evaluation using standardized tools. Results: The prevalence of tokophobia among parturients in the study population was determined, with findings indicating the extent of fear experienced by pregnant women in relation to childbirth. Additionally, the effectiveness of the nurse-led intervention in improving birth experiences was evaluated through comparison with a control group. Analysis of data revealed notable improvements in birth experiences among participants who received the nurse-led intervention, suggesting its beneficial impact in alleviating tokophobia and promoting positive childbirth experiences. Conclusion: This study sheds light on the prevalence of tokophobia among parturients in a tertiary care hospital setting in Kolkata and highlights the importance of addressing this fear to enhance birth experiences. The findings underscore the significance of nurse-led interventions in providing tailored support and guidance to pregnant women, ultimately contributing to improved childbirth outcomes and maternal well-being. Further research and implementation of similar interventions are warranted to advance maternal care practices and mitigate tokophobia-related concerns in childbirth settings.
Keywords: Prevalence; Tokophobia; birth experience; nurse-led intervention; tertiary care hospital